Subcultural Tastes in Latvia 2002-2010: The Content of Style - Daugavietis, Jānis; Lāce, Ilze (Studies of Transition States and Societies, 2011)
By carrying out a quantitative analysis of the musical taste of secondary school pupils, we attempt to understand how their tastes are formed, what their ‘subcultural element’ is and how it has changed over an eight-year period. Both in the classification of tastes and in the explanation of their meaning, as well as in the interpretations of the concept of subculture, we employ a group of conceptually related theories: Pierre Bordieu’s ‘sociology of taste’ and Richard Peterson’s thesis of omnivorism; as well as traditional and postmodern theories of subculture. Analysing the subcultural musical tastes, we conclude that the data from the 2010 questionnaire shows a far more ‘postmodern’ musical taste than that of the 2002 questionnaires. The distinctions between the groups of musical tastes are not as pronounced, the principles by which they are formed are less strict, and their content is more heterogeneous. Analysing the social factor (structure) and the relation of taste, a similar trend is observable – the homologous effect is weakening, although in certain cases it is still evident, namely in relation to gender and ethnicity.
Keywords: music; subcultures; Latvia; sociology